Questioning the policy of improving the quality of students through the research program and publication of scientific work at the postgraduate UIN Prof. Kh Saifuddin Zuhri Purwokerto - Sunhaji,; Umi Khomsiyatun,; Farhati Rizka Novianti,; Deva Mega Istifarriana,; Ade Eka Pradana, (Technium Social Sciences Journal, 2024)
Universities have an important role in training students in orientation and assimilation of knowledge through research and publication of scientific papers, especially in the era of society 5.0. Understanding and knowledge seem to be the only things that guarantee the social and economic progress of society that is not eroded over time. The Policy for Improving the Quality of Students through the Research Program and Publication of Postgraduate Student Scientific Work is an important initiative in advancing higher education and strengthening the role of students in their contribution to knowledge and scientific development. This research aims to describe how this program has contributed to improving the quality of postgraduate students, as well as its impact on the development of research and publication of students' scientific work.This research method uses a descriptive qualitative approach with literature study research as direct data. Data collection techniques by collecting published scientific papers from postgraduate students. To optimize the results of data collection, an article search was carried out from Google Scholar using the search terms names of postgraduate students who were used as research objects. Qualitative data analysis consists of three series: data reduction, data presentation and conclusion drawing. The research results show that: First, the condition of the quality of research activities carried out by Postgraduate students at UIN Prof. K.H. Saifudin Zuhri Purwokerto is doing well. Second, Policy and Implementation of Increasing the Quality of Students Based on Research and Scientific Writing at the UIN Postgraduate Program, Prof. K.H. Saifuddin Zuhri Purwokerto is stated in Circular Letter Number: 354/Un.19/D.PPs/PP.009/4/2022 concerning Publication of Scientific Work for Postgraduate Students at the State Islamic University of Professor Kiai Haji Saifuddin Zuhri Purwokerto in 2022. In its implementation, postgraduates participated supports this policy by organizing various supporting activities.